Accuracy and Reliability of Oral Exfoliative Cytology in Age Estimation: An Observational Study - Naseemoon Shaik; Vivek Anne; Saraswathi Saisupraja Mantha; Medapati Murali Jogi Reddy; Vidya Priyadarshini; B Tanuja; Sriharsha Pudi (Journal of Pharmacy and Bioallied Sciences, 2024)
Aim and Objectives: Age and gender identification are critical in forensic investigations, especially for unidentified human bodies. This study explores differences in nuclear size, nuclear area, and nuclear-cytoplasmic ratio between healthy individuals and those with physiological or pathological conditions, aiming to understand how these variations may influence age estimation. Materials and Methods: Following ethical clearance, the study was conducted on 80 participants aged 20–35 years, who were divided into four groups of 20 each, Group 1: Healthy individuals; Group 2: Individuals with physiological variations; Group 3: Individuals with pathological variations; and Group 4: Individuals with acquired conditions. Buccal cell samples were collected using a moistened tongue blade. Measurements of cell size, nuclear dimensions, nuclear area, and the nuclear-cytoplasmic ratio were taken. Results: Significant differences in nuclear and cell sizes were observed among participants with acquired conditions and metabolic disorders compared to healthy controls. Conclusion: The study suggests that systemic diseases and tobacco use (without visible oral lesions) can significantly affect cellular morphology, which may have implications for the accuracy of age determination in forensic analyses.